Assessing the benefits of corporate transparency. (2nd November 2004) - Thomas, Alison
Capital market efficiency is enhanced through improved quality of corporate reporting. Credible information, however, is costly to gather and disseminate. A practical methodology is thus required to determine the most cost effective way of evolving a company's communication strategy over time. To this end, this paper addresses three key questions: What information is required to provide confidence that the reported financial performance is both an accurate reflection of the value creating activities of management and sustainable over time? Why should companies report this information? What are the economic benefits? How, in practical terms, can companies start to frame their long-term reporting strategy? The journey that this paper suggests is not straightforward - indeed, for many, it will start with a hard look at the quality of internal information systems. However, recent events have underscored the fact that the costs of inaction are too high to ignore.